Agricultural Productivity, Hired Labor, Wages and Poverty : Evidence from Bangladesh - Emran, Shahe; Shilpi, Forhad (World Bank Group, Washington, DC, 2014)
This paper provides evidence on the effects of agricultural productivity on wage rates, labor supply to market oriented activities, and labor allocation between own farming and wage labor in agriculture. To guide the empirical work, this paper develops a general equilibrium model that underscores the role of reallocation of family labor engaged in the production of non-marketed services at home (`home production'). The model predicts positive effects of a favorable agricultural productivity shock on wages and income, but the effect on hired labor is ambiguous; it depends on the strength of reallocation of labor from home to market production by labor surplus and deficit households. Taking rainfall variations as a measure of shock to agricultural productivity, and using subdistrict level panel data from Bangladesh, this paper finds significant positive effects of a favorable rainfall shock on agricultural wages, labor supply to market work, and per capita household expenditure. The share of hired labor in contrast declines substantially in response to a favorable productivity shock, which is consistent with a case where labor-deficit households respond more than the labor-surplus ones in reallocating labor from home production.